Exchange of Microbiomes in Plant-Insect Herbivore Interactions - A. M. Pirttilä; V. Brusila; J. J. Koskimäki; P. R. Wäli; A. L. Ruotsalainen; M. Mutanen; A. M. Markkola (mBio, 2023)
ABSTRACT Prokaryotic and eukaryotic microbial symbiotic communities span through kingdoms. The vast microbial gene pool extends the host genome and supports adaptations to changing environmental conditions. Plants are versatile hosts for the symbionts, carrying microbes on the surface, inside tissues, and even within the cells. Insects are equally abundantly colonized by microbial symbionts on the exoskeleton, in the gut, in the hemocoel, and inside the cells. The insect gut is a prolific environment, but it is selective on the microbial species that enter with food. Plants and insects are often highly dependent on each other and frequently interact. Regardless of the accumulating evidence on the microbiomes of both organisms, it remains unclear how much they exchange and modify each other’s microbiomes. In this review, we approach this question from the point of view of herbivores that feed on plants, with a special focus on the forest ecosystems. After a brief introduction to the subject, we concentrate on the plant microbiome, the overlap between plant and insect microbial communities, and how the exchange and modification of microbiomes affects the fitness of each host.